Delivery of carbon, nitrogen, and sulfur to the silicate Earth by a giant impact - Grewal, Damanveer S. (Sci Adv, 2019)
Earth’s status as the only life-sustaining planet is a result of the timing and delivery mechanism of carbon (C), nitrogen (N), sulfur (S), and hydrogen (H). On the basis of their isotopic signatures, terrestrial volatiles are thought to have derived from carbonaceous chondrites, while the isotopic compositions of nonvolatile major and trace elements suggest that enstatite chondrite–like materials are the primary building blocks of Earth. However, the C/N ratio of the bulk silicate Earth (BSE) is superchondritic, which rules out volatile delivery by a chondritic late veneer. In addition, if delivered during the main phase of Earth’s accretion, then, owing to the greater siderophile (metal loving) nature of C relative to N, core formation should have left behind a subchondritic C/N ratio in the BSE. Here, we present high pressure-temperature experiments to constrain the fate of mixed C-N-S volatiles during core-mantle segregation in the planetary embryo magma oceans and show that C becomes much less siderophile in N-bearing and S-rich alloys, while the siderophile character of N remains largely unaffected in the presence of S. Using the new data and inverse Monte Carlo simulations, we show that the impact of a Mars-sized planet, having minimal contributions from carbonaceous chondrite-like material and coinciding with the Moon-forming event, can be the source of major volatiles in the BSE.